Wertschöpfungsketten in NRW im Kontext der Energiewende: Eine Metaanalyse bezüglich Stahl, polymeren Werkstoffen und dem Anlagenbau in der erneuerbaren Energiewirtschaft - Georg Kobiela; Daniel Vallentin (Wuppertal Institut für Klima, Umwelt, Energie, 2016)
Im Zuge der Energiewende steht die Industrie in NRW vor der substantiellen Herausforderung großer infrastruktureller Veränderungen. Dies bezieht sich auf den Energiebedarf, die Treibhausgasemissionen und den allgemeinen Ressourcenbedarf. Hierzu ist ein Zusammenspiel der industriellen mit den öffentlichen Akteuren vonnöten. Dies umfasst neben politischer Unterstützung und dem Nutzen von Marktmechanismen ist auch Regulierung, um diese Transformation zu unterstützen und voranzubringen. Die Steuerbarkeit solcher Prozesse hängt jedoch auch stark davon ab, in welchem Umfang die entlang der oftmals komplexen Wertschöpfungsketten ablaufenden industriellen Prozesse innerhalb NRWs angesiedelt sind. Hierzu muss neben dem technischen und wirtschaftlichen Möglichkeiten einer solchen Veränderung der Grad der Geschlossenheit der entsprechenden Wertschöpfungsketten betrachtet werden. Hierzu werden hier exemplarisch drei Wertschöpfungsketten betrachtet: Eisen- und Stahlproduktion, Chemie mit dem Fokus auf polymere Faserverbundwerkstoffe, und der Anlagenbau für die erneuerbare Energiewirtschaft. Diese wurden so ausgewählt, dass sie sowohl eine große strategische, wirtschaftliche bzw. seitens des Energiebedarfs und der Treibhausgasemissionen quantitative Relevanz für die Energiewende speziell in NRW haben, als auch unterschiedliche Arten der äußeren Anbindung, der internationalen Konkurrenz und der internen Governancestruktur aufweisen. Alle drei betrachteten Wertschöpfungsketten weisen eine ungenügende Geschlossenheit auf. Dies impliziert die Notwendigkeit einer Einbindung weiterer Regionen und höherer politischer Ebenen in den Transformationsprozess. NRW kann somit als eine Schlüsselregion verstanden werden, die zum Gelingen der Energiewende entscheidende Beiträge leisten kann - jedoch ist eine enge Kooperation mit weiteren deutschen Bundesländern wie auch den umgebenden Industrieregionen des europäischen Auslands notwendig. – – The industrial landscape in North Rhine-Westphalia faces substantial challenges in the context of the German energy transition (Energiewende). To facilitate a successful transition, large parts of the industrial infrastructure need to be transformed. This is both about the overall energy consumption, as well as the emission of greenhouse gases. Further on, the general consumption of natural resources needs to be considered. For such a transition, the interplay between industry and public actors is important. Political support, as well as regulation, play crucial roles. This reaches from setting up an appropriate market frame to enable self-improving process via market forces, over public support via funding and pilot projects, up to tariffs and other regulatory means. In how far it is possible to influence and shape these processes depends to large extents upon the level up to which the frequently rather complex value chains are located in NRW. Together with the technical and economic options for such changes, the degree to which a value chain can be regarded as closed is therefore a crucial factor. In this study, three exemplary value chains from different industry sectors are considered. These were selected in such a way that they yield strategic, economic and ecologic (in terms of energy consumption and greenhouse gas emissions) relevance for NRW. Further more, they display different ways how they are connected to the outside, face international competition and possess different kinds of internal governance structures. The selected value chains were those of iron and steel production, chemistry with a focus on fiber enforced polymers, and plant manufacturing for renewable energy generation with a focus on wind energy. A set of both quantitative and qualitative criteria was generated, yielding deeper insight into these value chains. This study rests on a meta analysis of already existing academic studies and sources from the respecting industries. The data from these sources was brought together to form a synthesis. Beyond this, potential ways to influence and support the desired transformation processes are sketched. All three value chains are only insufficiently closed. Therefore, further regions and political levels need to be part of the transformational process. NRW can be understood as a key region, with the potential to offer crucial support - but the challenges can only be met in close cooperation with other German states as well as with the surrounding industrial regions in the neighboring European countries. The results can help support the discussion for a competitive transformation of the industry in NRW toward a less unsustainable economic conduct. In this, it is not yet set whether such a necessary transition might simply align with the paradigm of so-called "green growth", or might also have the potential to help a transition toward a post growth economy, if appropriately combined with further concepts.
urn:nbn:de:bsz:wup4-opus-64917
Keywords: 330